Unveiling the Microbial Signatures of Arabica Coffee Cherries: Insights into Ripeness Specific Diversity, Functional Traits, and Implications for Quality and Safety - Gabriela N. Tenea; Victor Cifuentes; Pamela Reyes; Marcelo Cevallos-Vallejos (Foods)
Arabica coffee, one of the most valuable crop commodities, harbors diverse microbial communities with unique genetic and functional traits that influence bean safety and final coffee quality. In Ecuador, coffee production faces challenges due to the spread of pathogenic organisms across cultivars, leading to reduced yields and compromised quality. This study employed a shotgun metagenomic approach to characterize the indigenous microbial diversity present in the cell biomass of fermented coffee cherries from three Coffea arabica varieties: Typica (Group A), Yellow Caturra (Group B), and Red Caturra (Group C), originating from the Intag Valley in northern Ecuador, at two ripe stages: green (immature fruits) and ripe (red/yellow mature fruits). Gene prediction and functional annotation were performed using multiple databases, including EggNOG, COG, KEGG, CAZy, CARD, and BacMet, to explore the potential impact of microbial communities on bean quality and safety. Metagenomic sequencing generated over 416 million high-quality reads, averaging 66 million clean reads per sample and yielding a total of 47 Gbps of data. Analysis revealed distinct differences in species abundance based on the coffee variety and ripening stage. A total of 799,658 protein-coding sequences (CDSs) were predicted, of which 205,937 genes were annotated with EggNOG, 181,723 with COG, 155,220 with KEGG, and 10,473 with CAZy. Additionally, 432 antibiotic resistance genes (ARGs) were identified using CARD, and 8974 biocide and metal resistance genes (BMRGs) were annotated with BacMet. Immature cherries exhibited enriched pathways associated with resistance to antibiotics such as fluoroquinolones, penams, rifamycin, macrolides, carbapenems, and cephalosporins. The abundance of these pathways varied with the ripening stage and variety. Furthermore, green cherries showed a significant increase in BMRGs associated with resistance to substances including hydrochloric acid, copper, nickel, hydrogen peroxide, arsenic, and zinc. Among mature cherries, Typica and Red Caturra shared similar profiles, while Yellow Caturra displayed a divergent microbial and functional profile. These study findings emphasize the interplay between microbial diversity, ripening stages, and coffee varieties, providing a foundation for innovative approaches to enhance coffee quality through microbiome management.